Analysis of Risk Factors for Length of Hospitalization in Patients With Type 2 Diabetes Mellitus - Grace Lucyana Koesnadi; Raja Van Den Bosch Sihotang; Michelle Adelia Suwarno; Auron Saka Ibrahim; Jovansha Ariyawan; Toha Saifudin (Universitas Airlangga, 2026)
Introduction: Diabetes Mellitus (DM) is a chronic metabolic disorder characterized by persistent hyperglycemia due to impaired insulin secretion, insulin action, or both. This study aimed to analyze risk factors influencing the length of hospital stay (LOS) among patients with Type 2 Diabetes Mellitus (T2DM) at Universitas Airlangga Hospital in 2023. Methods: A quantitative observational study with a cross-sectional design was conducted using secondary data from 75 inpatient medical records. Survival analysis methods, including Kaplan–Meier estimation and Cox proportional hazards regression, were applied to evaluate factors associated with LOS. Results: The mean LOS was 3.89 ± 3.22 days, and the mean age was 58.37 ± 11.16 years. Patients aged >65 years had a longer LOS (5.64 days) compared to younger groups. Based on the Cox regression model, age was identified as the only variable that significantly influenced LOS (p < 0.05), with younger patients having a higher probability of earlier discharge. Conclusion: In conclusion, age is a significant predictor of hospitalization duration in T2DM patients. These findings highlight the importance of age-specific management strategies to optimize hospital resource utilization and patient outcomes